Are the carriers of diffuse interstellar bands and extended red emission the same?. Issue 4 (28th January 2020) - Lai, Thomas S-Y; Witt, Adolf N; Alvarez, Carlos; Cami, Jan
ABSTRACT: We report the first spectroscopic observations of a background star seen through the region between the ionization front and the dissociation front of the nebula IC 63. This photodissociation region (PDR) exhibits intense extended red emission (ERE) attributed to fluorescence by large molecules/ions. We detected strong diffuse interstellar bands (DIB) in the stellar spectrum, including an exceptionally strong and broad DIB at λ4428. The detection of strong DIBs in association with ERE could be consistent with the suggestion that the carriers of DIBs and ERE are identical. The likely ERE process is recurrent fluorescence, enabled by inverse internal conversions from highly excited vibrational levels of the ground state to low-lying electronic states with subsequent transitions to ground. This provides a path to rapid radiative cooling for molecules/molecular ions, greatly enhancing their ability to survive in a strongly irradiated environment. The ratio of the equivalent widths (EWs) of DIBs λ5797 and λ5780 in IC 63 is the same as that observed in the low-density interstellar medium with ultraviolet (UV) interstellar radiation fields (ISRF) weaker by at least two orders of magnitude. This falsifies suggestions that the ratio of these two DIBs can serve as a measure of the UV strength of the ISRF. Observations of the nebular spectrum of the PDR of IC 63 at locations immediately adjacent to where DIBs were detected failed to reveal any presence of sharp emission features seen in the spectrum of the Red Rectangle nebula. This casts doubts upon proposals that the carriers of these features are the same as those of DIBs seen at slightly shorter wavelengths.